Membangun Etika Publik melalui Harmonisasi Akhlaq dan Hukum Islam - Sumarta, Sumarta; DwiKurniadi, Septian (Fakultas Hukum dan Ekonomi Syariah Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2024)
Building public ethics is a crucial aspect of creating a just and harmonious society. The harmonization between akhlaq (Islamic ethics) and Islamic law plays a central role in this process. Akhlaq, as the moral dimension internalized by individuals through education and social environment, provides the foundation for good and responsible behavior. Islamic law, with its comprehensive normative structure, offers clear and firm guidelines for regulating social interactions and maintaining public order. The combination of both allows for the formation of public ethics based not only on legal compliance but also on high moral values. This research highlights the importance of synergy between akhlaq and Islamic law in building public ethics, focusing on practical applications in society. Through literature analysis and case studies, it is found that this harmonization can enhance individual compliance with the law, strengthen social justice, and promote a collective sense of responsibility. In conclusion, the integration of akhlaq and Islamic law is key to building strong and sustainable public ethics.